SYSTEMATIC LITERATURE REVIEW (SLR): THE ANALYSIS OF THE JUVENILE DELINQUENCY TRIGGER FACTORS AND THE HANDLING EFFORTS - sulthon, sulthon; Munir, Muh Misbahul (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2024)
Â Adolescence is a stage in development experienced by individuals that is different from previous periods. In this period individuals face puberty which is marked by the transition from childhood to adulthood. At this time, teenagers face doubt, uncertainty, emotional instability, so that their actions often deviate from values and norms, this deviation is influenced by many aspects both from within and from outside. The aim of this research is to identify, analyze, study and conclude the factors that trigger juvenile delinquency and efforts to overcome it. The method used in the research is library research with a systematic literature review (SLR) approach. Data collection was carried out using journal search techniques with the keywords "juvenile delinquency", "triggers or causes of juvenile delinquency", "efforts to overcome juvenile delinquency", from journals indexed by Sinta or Google Scholar, and Scopus which were published in the last six years, namely 2018-2023, Data validity testing is carried out by selecting journals based on inclusion and exclusion criteria which will be reviewed is currently analyzing the data by processing all collected articles identified based on inclusion and non-inclusion, place, index, content, then described and analyzed and concluded. The results of the research show that the triggering factors for juvenile delinquency consist of internal and external factors, internal factors namely from within oneself due to an identity crisis, weak control and self-control, and lack of discipline; while external factors include family environment, lack of attention and affection from parents, broken home, low knowledge and practice of religion, poor social environment, school environment, negative influence of peers, weak economy, uncontrolled use of social media information technology, low level of education, and carefree upbringing, while efforts are being made to control it with a strong understanding and practice of religion, democratic parenting, attention and affection and treatment of teenagers according to their age, giving good role models, giving trust and responsibility, training entrepreneurial entrepreneurs, and collaboration with youth organizations in providing sports activities and religious studies. This research provides information about the factors that cause juvenile delinquency and its prevention so that parents or schools can reduce or prevent juvenile delinquency.